ANALYSIS OF THE DETERMINED LOCATION OF THE SUBMARINE BASE IN THE AREAS OF FLEET COMMAND III USING HYBRID MCDM METHODS DELPHI, ANP, AND SAW - Taufik Ramdhan; Suparno Suparno; Joko Purnomo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
The formation of the III Fleet Command in the development and development of the Indonesian Navy's strength has a strategy of developing a strong posture. The development of the TNI AL posture that has been determined includes the level of ability, strength, and pattern of strength degrees. One of the strength postures built and developed is submarines. To support the optimization of submarine operations in the Koarmada III area, it is necessary to build supporting facilities to extend the capability of the submarine's operating range, namely special submarine base facilities. The purpose of this study is to analyze the criteria that are considered and determine the priority of the location of the submarine base in the Koarmada III area. This research was carried out in three stages, namely the stage of determining the criteria using the Delphi method, the stage of weighting the criteria using the ANP method, the stage of ranking alternative locations using SAW. In the first stage of the analysis, ten main criteria were found in determining the location of the submarine base which were then used as the basis for the second stage of analysis, namely the determination of the structure and weighting of the ANP. The results of the weighting of the criteria are used for the third analysis process, namely the ranking of alternatives using the SAW method. The results of the SAW processing prove that Ambon is the main priority in determining the location of the submarine base in the Coarmada III Region with the SAW value = 0.858 with a weight of 27.8%. The results of this study are expected to be a consideration for the leadership of the Indonesian Navy in determining the location of submarines in the future. Keywords: Submarine Base, Delphi, ANP, SAW